Parental engagement in child's learning and development - Department of Social Services (Department of Social Services, 2015)
This article uses five waves of data from Footprints in Time to explore parental engagement in Indigenous children's learning and development.
Footprints in Time: The Longitudinal Study of Indigenous Children: Report from Wave 5
Keywords: Education and Training -- Early Childhood; Children -- Indigenous; Learning, education and training; Children; Education and Training; Early Childhood; Indigenous; Learning, education and training